Developing DRTA (Directed Reading Thinking Activity) Strategy Teaching Materials for Elementary School Students in Improving Reading Prediction Skills - Otang Kurniaman; Eddy Noviana; Zufriady Zufriady (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study was to develop appropriate reading teaching materials for use in elementary schools. The study used the 4D research method by developing reading teaching materials using the DRTA strategy in predicting reading. Several analyzes the defining phase of needs analysis, including curriculum, concepts, and tasks. While in the study of students about the suitability of teaching materials developed with the level of student development. The design phase of teaching material development begins with the design of RPP with the curriculum. The format and preparation of teaching materials are modified from the cover, preface, table of contents, usage instructions, concept maps, competencies to be achieved, tasks, and work instructions. The development phase includes the validation of teaching materials and RPP. Then the product is tested to see the practicality and effectiveness of the teaching materials that have been developed. Research results explained RPP validation for aspects of learning objectives with an average of 94 very valid and aspects of learning material with 100 very valid. The dissemination stage of the assessment process for reading skills is done using an assessment rubric. The average class value at meeting 1 is 93.34. The second meeting is 89.142. The third meeting is 85.92 with an overall average of 89.46 with a very good category. The assessed aspects are several student skills, from predicting reading activities, reading techniques, filling in the meaning of words that have not been understood, writing down the main contents of the reading text, and summarizing the summary of the reading contents.